The Complex Interplay between Religion and Healthcare in Nigeria: Historical Roots, Current Dynamics, and Future Implications - Temitope, Oyebanji Israel (Darul Yasin Al Sys, 2025)
This study explores the complex interplay between religion and healthcare in Ibadan, Nigeria, with a focus on how religious beliefs shape health-seeking behaviour, influence healthcare delivery, and generate specific challenges at the intersection of faith and medicine. In a society where religion deeply informs perceptions of illness, wellness, and healing, understanding its role in health systems is essential. Despite the prominence of religion in Nigerian life, limited research has addressed how religious values align or conflict with evidence-based medical practices and their implications for equitable healthcare access. This study seeks to fill that gap by addressing three core questions: (1) How do religious beliefs affect health-seeking behaviour? (2) What roles do faith-based organisations (FBOs) play in complementing state healthcare services? (3) What ethical dilemmas and resource disparities emerge from the integration of religious and medical frameworks? Employing a mixed-methods approach, the study gathered data through surveys (n = 300), semi-structured interviews (n = 20), and a comprehensive literature review, analyzed within the framework of Social Constructivist Theory. Findings show that 66.78% of respondents attribute illness to spiritual causes and often prioritize faith-based interventions. FBOs operate 35% of healthcare facilities, offering trusted and affordable care, yet face challenges such as commercialisation and uneven urban-rural service distribution. Ethical conflicts, particularly concerning contraception and blood transfusions highlight tensions between religious doctrine and medical ethics. The study recommends enhancing collaboration between religious and governmental health initiatives, incorporating cultural sensitivity training for healthcare providers, and strengthening rural healthcare infrastructure. These strategies aim to harmonize spiritual values with scientific care, improving health outcomes within Nigeria’s diverse sociocultural landscape.